2009
DOI: 10.1080/13693780802342537
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin involvement in granuloma formation and in the severity ofParacoccidioides brasiliensisinfection

Abstract: The participation of osteopontin (OPN) in Paracoccidioides brasiliensis infected mice, its association to granulomatogenesis, severity of infection, pattern of lesions, nitric oxide (NO) levels and fungal load were evaluated in this investigation. Immunohistochemistry analysis showed marked OPN staining in extracellular matrix and in macrophages and multinucleated giant cells at the center of lesions, suggesting a possible role of OPN in the distribution of these cells within the granulomas. At 15 days post-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 24 publications
4
16
0
Order By: Relevance
“…However, regardless of etiology, common mechanisms are involved in the formation of granulomas. A series of complex, coordinated events brings about the recruitment of macrophages, T cells, cytokine release, and subsequent transformation of macrophages into epithelioid and multinucleated giant cells (17,20,(29)(30)(31)(32). Previous studies administered single and multiwall carbon nanotubes, and reported inflammatory lung responses (10,12,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, regardless of etiology, common mechanisms are involved in the formation of granulomas. A series of complex, coordinated events brings about the recruitment of macrophages, T cells, cytokine release, and subsequent transformation of macrophages into epithelioid and multinucleated giant cells (17,20,(29)(30)(31)(32). Previous studies administered single and multiwall carbon nanotubes, and reported inflammatory lung responses (10,12,33).…”
Section: Discussionmentioning
confidence: 99%
“…Osteopontin is a key cytokine recently shown to associate with granulomatous inflammation, regardless of cause (17)(18)(19)(20). Osteopontin induces leukocyte chemotaxis, and is produced by alveolar macrophages.…”
mentioning
confidence: 99%
“…On the other hand, at later phase of infection, resistant mice showed a higher IFN-c staining in lymphomononuclear cells compared with susceptible mice, suggesting the presence of protective immune mechanisms to the control of fungal dissemination through the high activation status of phagocytes, as previously described . Therefore, susceptible mice although able to produce IFN-c since the early stage of the infection, could not control the fungal dissemination, as demonstrated by the several loose granulomas containing viable fungal cells, indicating their incapacity to control the infection, and confirmed by the higher fungal load in omentum lesions of B10.A than in A/J mice previously observed by the same authors (Nishikaku et al, 2008).…”
Section: Discussionmentioning
confidence: 70%
“…In our experimental model of P. brasiliensis infection, we could detect distinct patterns of ECM components using immunohistochemical reactions (Xidieh et al, 1999;Nishikaku & Burger, 2003a, b), the presence of some cytokines (Nishikaku & Burger, 2003a;Nishikaku et al, 2008) and of proteolytic enzymes (Nishikaku et al, 2009a) at the lesions of infected mouse strains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation